Analisis Pengaruh Variabel Fasilitas Perumahan, Kesehatan, dan Standar Hidup Layak, Terhadap Pendidikan dan Kemiskinan di Provinsi NTT - Vievien Abigail Damu Djara; Adrianus Kabubu Hudang (Jurnal Statistika Terapan (ISSN 2807-6214), 2025)
East Nusa Tenggara (NTT) Province in 2024 is included in the top 5 (five) with the highest percentage of poor people in Indonesia, so it needs to be a concern for researchers in studying poverty in NTT. Several variables used in this study refer to the dimensions of the Human Development Index calculation and several previous studies. The unit analysis in this study is all regency/municipality in NTT. The Structural Equation Modeling-Partial Least Square (SEM-PLS) was considered. The results at a significance level of five percent show that social variables (decent housing, improved drinking water, and improved sanitation) had a significant effect in reducing poverty in NTT. This social variable had the greatest effect in reducing poverty in NTT compared to other variables used in this study. Social variables also had a significant effect in increasing health variables, and then this health variable had a significant effect in reducing poverty in NTT. The result of this study also found that the decent standard of living variable had a significant effect in increasing education and health in NTT. The results of this study have a Goodness of Fit (GoF) index of 0.709, which means that the model is fit for use in the analysis.